IMPLEMENTATION OF PROJECT-BASED LEARNING (PjBL) ON IPAS LEARNING MATERIALS IN THE MERDEKA CURRICULUM AT MUHAMADIYAH MUJAHIDDIN ELEMENTARY SCHOOL - Irfan; Mohamad Agung Rokhimawan; S Nudia Mastur; Noor Alfi Fajriyani; Kharisma Romadhon; Melisa Paulina (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
For students, the Merdeka curriculum has the potential to provide relevant learning opportunities in line with PjBL objectives. The research in this paper provides further explanation of how the PjBL model plays a role in IPAS learning subjects and the idea of Merdeka curriculum that emphasizes projects. Case study research is a type of study conducted in this paper. The research uses a qualitative methodology. The steps are observation, interviews, and documentation are used as a data collection approach. During the observation, observations come from observations and initial conditions. Grade IV and V teachers are interviewed and so are grade IV and V students. The information was the data collected from published literature. Data from triangulation and validity tests are used to validate the findings. The research results at Muhamadiyah Mujahidin Elementary School on the use of Project Based Learning on the IPAS learning material content in the independent curriculum reveal that six PjBL syntaxes consist of project determination, design of project completion steps, preparation of project implementation schedule, project completion with facilities and teacher monitoring, preparation of reports and presentations or publication of project results, and evaluation process and project outcomes. The use of PjBL through its syntax at SD Muhamadiyah Mujahidin indicates the regularity of students and teachers in following this PjBL syntax. In order to implement project-based learning methods successfully, it is relevant to the findings of the six phases. Students who actively participate in this co-curricular activity tend to be inspired more by the implementation of the PjBL model, which allows the fulfillment of other appropriate requirements besides cognitive activities.